The great Lady: restoring her story - Barker, Margaret (Sheffield Phoenix Press, 2023)
"In this, the eighteenth of Margaret Barker's sequence of works on Temple Theology, she returns to give further and fuller attention to the figure of the Great Lady. Barker surveys the Hebrew Bible, Dead Sea Scrolls, New Testament and noncanonical texts from both Jewish and Christian traditions--and undertakes a re-telling of the story of the Great Lady's shadowy but enduring presence in community memory and later writings. This extensive volume has three parts: The Great Lady in the first temple, revered as the heavenly Mother of the Davidic kings until King Josiah's purge in 623 BCE; The Great Lady in the Book of Revelation, present in her ancient symbols and the hopes of her prophets, which Jesus knew; The Great Lady hidden in the teaching of Jesus and stories about him, explaining why she was so important in the world of the early Church. This close study of the Great Lady shows new significance in the words of the Hebrew prophets and the Qumran texts, and offers a new context for early Christian writings and so-called Gnostic texts. Barker shows how the first Christians brought the Great Lady back to their Temple Theology. She proposes that in this community Jesus her Son was the expected Melchizedek and great high priest, and Mary of Nazareth was hounoured as the Mother of God." --